Tinjauan Persentase Penutupan Vegetasi(PPV) Di Das Indragiri Hulu Stasiun Lubuk Ambacang Tahun 2018 - Triyono, Triyono; H, Yohanna Lilis; Fauzi, Manyuk (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The Indragiri Hulu watershed often experiences floods. This flood is caused by the overflow of the Indragiri river during the rainy season. This flooding is also caused by developments in land use change. This condition can threaten the existence of communities around the river area. The purpose of this study was to analyze the value of Vegetation Closure Percentage (PPV) in the upstream river of Indragiri at Lubuk Ambacang Station. The analysis was carried out using a Geographic Information system by digitizing the existing land classes in the Upper Indragiri Basin at the Lubuk Ambacang Station using data obtained from satellite imagery. The results showed that the PPV value in 2018 was equal to 81.48% and the watershed was included in good sabbath conditions. This is caused by watershedIndragiri upstream of Lubuk ambacang station which is dominated by land class with a percentage of 62.11%.Keyword:Vegetation Closure Percentage, Landuse, Indragiri Watershed, GIS